2014
DOI: 10.3109/02699206.2014.966394
|View full text |Cite
|
Sign up to set email alerts
|

Rates of auxiliaryisandarein African American English speaking children with specific language impairment following language treatment

Abstract: The purpose of this exploratory study is to examine rates of auxiliary is and are across dialect patterns produced by African American English with specific language impairment (AAE-SLI) children following language treatment. The following research question is asked: Do AAE-SLI children exhibit rates of auxiliary is and are across dialect patterns consistent with previous reports of typically developing children and adult AAE speakers? A pre-/post-test design was used to identify patterns in which auxiliary is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This linguistic information is important to understand so that dialect effects can be incorporated into assessment and treatment expectations. Indeed, in at least one treatment study of AAE-speaking children with SLI, dialectspecific language growth was evident (Smith & Bellon-Harn, 2015). Before treatment, the children, aged 4-5 years, produced 160 predicates that could support is or are, and their percentages of overt marking were 6% and 7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This linguistic information is important to understand so that dialect effects can be incorporated into assessment and treatment expectations. Indeed, in at least one treatment study of AAE-speaking children with SLI, dialectspecific language growth was evident (Smith & Bellon-Harn, 2015). Before treatment, the children, aged 4-5 years, produced 160 predicates that could support is or are, and their percentages of overt marking were 6% and 7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Because of these same characteristics, which coincidentally also resemble the speech of children with SLI (Smith 2015), currently known as Developmental Language Delay, children speaking AAE have often been referred to a speech language pathologist. This unsubstantiated tendency to consider or even clinically evaluate AAE-speaking children's language as being at risk for a language disorder, or presenting characteristics that resemble a language disability, may be stemming from the fact that test norms and baseline information used by professionals (SLPs, teachers, psychologists) are typically obtained by children from "White middle-class MAEspeaking backgrounds" or comparative studies of "African American and White children" (Wyatt 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Previous SLI studies using a disorder within dialects framework have revealed three important findings regarding the marking of T/A in AAE and SWE: (a) Children with and without SLI express T/A using a large and diverse inventory of mainstream overt forms (e.g., cried, saw, fell), nonmainstream overt forms (e.g., had cried, had cry, kickeded, seen, falled, verbal -s with first-and second-person subjects), and nonmainstream zero forms (e.g., cryØ, seeØ, fallØ); (b) the relative frequencies at which these various forms are produced vary by a child's dialect (AAE vs. SWE) and T/A structure (e.g., past tense vs. verbal -s) 1 ; and (c) AAE-and SWE-speaking children with SLI often produce lower percentages of mainstream and nonmainstream overt forms and higher percentages of nonmainstream zero forms than same dialect-speaking TD controls (for a review of language sample studies, see Oetting, 2019; see also Hendricks & Adlof, 2020;Smith & Bellon-Harn, 2015).…”
mentioning
confidence: 99%